2020
DOI: 10.1532/hsf.3103
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Brain Protection With Histidine-Tryptophan-Ketoglutarate Solutions

Abstract: Background: Tissue-protective solutions increase resistance of cells to ischemic conditions. Especially in carotid and aortic arch surgeries where the brain perfusion is at risk, these solutions may be beneficial to prevent ischemic brain damage. This study was designed to demonstrate the effectiveness of histidine-tryptophan-ketoglutarate (HTK) solution in increasing resistance of brain tissue to ischemic conditions. Methods: Three separate randomized groups were created, each consisting of eight rabbits. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Wang et al (38) found that oral administration of tryptophan significantly improved depression and anxiety-like behaviors via the gut-brain-axis pathway in chronically and mildly stressed mice. Oğuz et al (39) found that carotid artery infusion of tryptophan-containing histidine-tryptophan-ketoglutaric acid solution significantly reduced the degree of ischemia and the number of apoptotic cells in rabbits with CIRI and effectively enhanced the resistance of the brain to ischemic conditions. Xanthine is a purine base commonly used as a mild stimulant.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (38) found that oral administration of tryptophan significantly improved depression and anxiety-like behaviors via the gut-brain-axis pathway in chronically and mildly stressed mice. Oğuz et al (39) found that carotid artery infusion of tryptophan-containing histidine-tryptophan-ketoglutaric acid solution significantly reduced the degree of ischemia and the number of apoptotic cells in rabbits with CIRI and effectively enhanced the resistance of the brain to ischemic conditions. Xanthine is a purine base commonly used as a mild stimulant.…”
Section: Discussionmentioning
confidence: 99%